Novel approaches to control browning of fresh-cut artichoke: Effect of a soy protein-based coating and modified atmosphere packaging - Ghidelli, Christian; Mateos, Milagros; Rojas-Argudo, Cristina; Pérez-Gago, María B. (2017)
A soy protein isolate (SPI):beeswax (BW) edible coating was optimized based on BW and L-cysteine (Cys) content to reduce the enzymatic browning of fresh-cut artichoke. The effect of this optimized coating, combined with different modified atmospheres (MA) to extend the shelf-life of cut artichokes, was studied during storage at 5 C. MAs were obtained by fluxing two gas mixtures (MA-A: 5 kPa O-2 + 15 kPa CO2; MAB: 80 kPa O-2) or by conventional passive MA (MA-P). Atmospheric conditions were used as the control. The use of 0.3 g/100 mL Cys combined with a SPI-BW edible coating (40 g/100 g BW, dry basis) helped control enzymatic browning and extended the commercial shelf-life of fresh-cut artichokes to 4 days without providing off-odors. The combination of the coating with MAs did not extend the shelf-life of artichoke slices, but helped maintain the product's antioxidant capacity as compared to the control packaging conditions. Given the high degree of perishability of untreated fresh-cut artichoke, a 4-day commercial period can be considered adequate to distribute sliced artichokes to local markets. However, more studies are required to further extend shelf-life. (C)2014 Elsevier B.V. All rights reserved.